Promoting designer oriented thinking through the experience of making - Ramli, Saiful Hasley; Rust, Christ; Chamberlain, Paul; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
This paper was a part of a research, investigating design methods to enhance creative collaborations between designers and expert users. This part essentially was explored through designing workshops participated by designers and a laboratory chemist. A practice led approach was adopted in which the writer acted both as a researcher and a designer, where observation and reflection served as the method of this work. Through the research, data were collected in the form of video recordings of an interview and a co-design session with the use of mock-ups. The design methods that were explored through this research have enabled expert users to employ designer oriented strategies in design collaborations. The analysis of these workshops has demonstrated that these collaboration strategies can enable the expert users to mobilize their professional experiences and knowledge in design collaborations. The outcome of this research supports the development of further research techniques as well as the refinement of the design method.